1985
DOI: 10.1300/j075v06n03_01
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Successful Implementation of Computer-Based Office Information Systems:

Abstract: Factors affecting implementation of computer-based office information systems are reviewed. Three broad categories are discussed-characteristics of innovative systems, implementing offices and organizations, and the implementation process itself, with particular attention paid to the latter. The review concludes with a discussion of the importance of non-technical factors in technological innovation and suggestions for issues of particular relevance to OBM researchers.The introduction of computers into offices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Utilization of new technology A well-accepted definition of the utilization of technology, that it is "the extent to which a technology is digested or absorbed into a firm," is found in Mankin et al (1984). This concept has been widely used in studies on technology and innovation, such as those by Kimberly (1979) and Zmud and Apple (1992).…”
Section: Support From Supplying Firmmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of new technology A well-accepted definition of the utilization of technology, that it is "the extent to which a technology is digested or absorbed into a firm," is found in Mankin et al (1984). This concept has been widely used in studies on technology and innovation, such as those by Kimberly (1979) and Zmud and Apple (1992).…”
Section: Support From Supplying Firmmentioning
confidence: 99%
“…For an operational definition of the utilization of technology, Leonard-Barton and Deschamps (1988) and Zaltman et al (1973) have suggested that the focus be on the extent to which the members of an organization are making use of the technology. Also, Mankin et al (1984) and Tolbert and Zucker (1983) recommended drawing on the bureaucratization of a new technology within the organization. These operational definitions of the utilization of technology have been used in various studies on technology and innovation management, including those by Marshall and Vredenburg (1992) and Swanson and Ramiller (1997).…”
Section: Support From Supplying Firmmentioning
confidence: 99%
“…Further, Attewell (1992) argues that complex IS innovations are `technologically demanding, fragile and lumpy', unlike the reliable, commodity-like innovations considered in diffusion theory. Implementing such innovations is an uncertain process of knowledge discovery, skill formation and the mutual adaptation of the technology and the organization (Mankin et al, 1985;Attewell, 1992). Managerial commitment plays a critical role in the uncertain process of adoption by facilitating solutions to the numerous contingencies that arise during the various stages of implementation (Sauer, 1993;Sabherwal and Elam, 1995).…”
Section: Implementation Process Theorymentioning
confidence: 99%
“…Ainsi, plusieurs auteurs ont insisté sur l'importance d'une communication hâtive et complète entre gestionnaires et employés, les premiers devant prodiguer aux seconds une information transparente et continue sur les raisons du changement, son déroulement et son évolution, ainsi que sur ses impacts (Kotter et Schlesinger, 1979 ;Mankin, Bikson et Gutek, 1985 ;Fredericksen, Riley et Myers, 1985 ;Haddad, 1996). La formation sur le SI peut être envisagée pour développer les compétences de l'employé, sur la base de son niveau d'éducation et de l'expérience qu'il pourrait avoir déjà acquise, et le préparer ainsi à utiliser le SI tout en développant sa confiance en soi et son sentiment d'efficacité personnelle.…”
Section: Cadre Conceptuelunclassified